Transforming cassava wastes to wealth as a climate-change mitigation strategy in Nigeria - Adedeji, Oluwaseun (Technical Centre for Agricultural and Rural Cooperation, 2019)
Cassava production and processing in Nigeria generates large quantities of hazardous wastes and residues. Aside from the environmental hazards, such wastes contribute to greenhouse gas (GHG) emissions. An innovative climate-smart intervention in Nigeria is to re-use the cassava peels in animal feeds. This reduces the demand for maize for feed, creates new business opportunities from waste, reduces the hazards of the waste and reduces GHG emissions.